How people with multiple sclerosis experience the influence of nutrition and lifestyle factors on the disease. Issue 24 (19th November 2020) - Karnoe, Astrid; Pedersen, Lise M.; Karlsen, Sashia; Boesen, Finn; Skovgaard, Lasse; Kayser, Lars
Abstract: Purpose: Increasing knowledge suggests that nutrition and lifestyle factors affect multiple sclerosis. This study explores how people with multiple sclerosis experience daily multiple sclerosis disease activity and the influence of nutrition and lifestyle factors (e.g., stress, sleep, and environmental temperature). Methods: Four phases mix qualitative and quantitative elements in an exploratory study. The initial two phases consisted of an exploratory study with 14 participants followed by 15 semi-structured interviews. Results from the two first phases were substantiated in a survey completed by 425 respondents (response rate: 42.5%). Finally, findings and inconsistencies were elaborated in three focus group interviews. Results: In the initial exploratory study, several of the participants linked nutrition and lifestyle factors to disease activity. Results from the semi-structured interviews showed that particularly stress, meat, fatty foods, and processed sugar were perceived to have a negative impact on disease activity, and some participants had experienced immediate effects of these factors on their disease activity. The survey supported these findings that were further elaborated in focus groups. Conclusion: People with multiple sclerosis perceive nutrition and lifestyle to affect daily disease activity. Individuals who have experienced links between their multiple sclerosis, and nutrition and lifestyle attribute some of these changes to e.g., stress, and the consumption of sugar, meat, and fatty food. Implications for rehabilitation: A majority of the participants in this study perceived nutrition and lifestyle factors to have an effect on their multiple sclerosis, particularly stress, meat, fatty foods, and processed sugar. Some participants with multiple sclerosis experienced that nutrition, stress, environmental temperature, and physical activity had a direct effect on the severity of daily symptom manifestations. Nutrition and lifestyle factors that potentially influence multiple sclerosis disease activity should be considered when organizing rehabilitation and care to better meet the needs of the individual with multiple sclerosis.